2018
DOI: 10.1111/cid.12648
|View full text |Cite
|
Sign up to set email alerts
|

The prosthetic abutment height can affect marginal bone loss around dental implants

Abstract: The present study suggests that implants with a higher prosthetic abutment show less MBL, with the abutment height recommended to not exceed 4 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…Statistical analysis of the relationship between abutment height and MBL showed that the incidence of MBL and the mean MBL decreased with increasing abutment height. They further claimed, contrary to our findings, that implants with a higher prosthetic abutment demonstrate less MBL and that the abutment height should not exceed 4 mm [8]. Evidence from Chen et al also suggests that abutment height has a role in determining the first marginal bone loss rate surrounding implants placed at the bone level.…”
Section: Table 2 Correlation Between Crown Height and Follow-up Mblcontrasting
confidence: 97%
“…Statistical analysis of the relationship between abutment height and MBL showed that the incidence of MBL and the mean MBL decreased with increasing abutment height. They further claimed, contrary to our findings, that implants with a higher prosthetic abutment demonstrate less MBL and that the abutment height should not exceed 4 mm [8]. Evidence from Chen et al also suggests that abutment height has a role in determining the first marginal bone loss rate surrounding implants placed at the bone level.…”
Section: Table 2 Correlation Between Crown Height and Follow-up Mblcontrasting
confidence: 97%
“…32 As the distance between the microgap and alveolar crest decreases, the microbial infiltration to the alveolar bone would increase. 33 Thus, the less-than-1-mm titanium adapter of the ASC abutment might have increased the microbial infiltration and caused the higher concentration of TNF-α in the AG. However, long-term follow-up is needed to observe the trend of IL-6 in these two types of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that investigated the correlation between height of implant abutment and peri-implant bone loss also used panoramic radiography and periapical radiography. And these studies showed significant results of the relationship between height of implant abutment and bone loss around the implant [20][21][22].…”
Section: Discussionmentioning
confidence: 96%